P126 GCA Hospital Standards (GHOST) - making a map of specialised services for the care of giant cell arteritis across England. (23rd April 2022) - Coath, Fiona L; Bukhari, Marwan; Ducker, Georgina; Griffiths, Bridget; Hamdulay, Shahir; Hingorani, Melanie; Horsbrugh, Candy; Jones, Colin; Lanyon, Peter; Mackie, Sarah; Mollan, Susan; Mooney, Janice; et al.
Abstract: Background/Aims: The objective of this project is to map services essential to delivering high quality care in giant cell arteritis (GCA) across England, identifying gaps in provision and thereby help to remove inequalities. To do this however, there must first be agreement on what these best practice services and standards are. Methods: A steering committee was formed comprising 18 expert representatives from the 13 clinical regions in England, including rheumatology, ophthalmology, allied health professional and patient representation. A modified Delphi process was commenced with each member initially providing five aspects of service they felt were essential for best practice GCA care. From the 90 answers, common themes were identified by creation of a word cloud and then condensed into domains of practice. These domains were then ranked by each member in order of perceived importance. The top 10 domains taken forward for further review were clinical pathways, patient access, Rheumatology involvement, Ophthalmology involvement, ultrasonography provision, temporal artery biopsy provision, PET-CT scan provision, glucocorticoid treatment, patient education and multi-disciplinary team working. Domains identified as separate areas but not quite making it into the top 10 were Tocilizumab provision, audit and governance and research. With the latter two in particular, it was felt these are overarching principles which should run through all aspects of clinical work. Group consultation was undertaken to discuss the relevant aspects, and from this, three quality metrics and one summary statement were devised for each domain. Rheumatology and Ophthalmology provision were amalgamated, as it was felt these were equally as important, with similar requirements. On the first pass of voting all except 'patient access' achieved over 75% agreement amongst the steering committee members. After group consultation and amendment, 'patient access' also achieved the minimum 75% agreement cut-off. The final statements can be seen in the table below. Results: Conclusion: By devising specific quality metrics in addition to the recommendation statements above, it is envisaged these standards can be easily used as an audit tool to identify gaps and development needs in GCA services. Disclosure: F.L. Coath: None. M. Bukhari: None. G. Ducker: None. B. Griffiths: None. S. Hamdulay: None. M. Hingorani: None. C. Horsbrugh: None. C. Jones: None. P. Lanyon: None. S. Mackie: None. S. Mollan: None. J. Mooney: None. J. Nair: None. E. O'Sullivan: None. A. Patil: None. J. Robson: None. V. Saravanan: None. M. Whitlock: None. C. Mukhtyar: None.